EFEKTIVITAS METODE EVERYONE IS A TEACHER HERE DALAM MENINGKATKAN MINAT PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS V MADRASAH IBTIDAIYAH AL ZAYTUN - Nur Afifah, Fadiyah; Kartini; Humaeroh, Iis (Sindoro: Cendikia Pendidikan, 2024)
This research was conducted because, in the Islamic Cultural History lessons, the teacher explained the material in a monotonous manner, using the lecture and assignment methods. These methods, which are considered monotonous, affected students and resulted in a lack of active participation during the learning process. Consequently, the material delivered did not leave a lasting impression that could influence students' interest and learning outcomes. Given this problem, the researcher attempted to improve the learning process of Islamic Cultural History by applying the "Everyone Is A Teacher Here" learning method. The type of research conducted was quantitative, with the specific type being a Quasi-Experimental design, using The Static Group Comparison Design. The research subjects were fifth-grade students, with the sample selected through simple random sampling. The results of the research indicated that the "Everyone Is A Teacher Here" method was effective in increasing students' interest in learning Islamic Cultural History. This was evident from the hypothesis test results, which showed that H0 was rejected and H1 was accepted, with a two-tailed t-test significance value of less than 0.05, specifically 0.000. Therefore, it can be concluded that the "Everyone Is A Teacher Here" method is effective in enhancing the interest of fifth-grade students at Al-Zaytun Islamic Elementary School in learning Islamic Cultural History in 2023. Keywords: interactive learning method, everyone is a teacher, Islamic cultural history.